Your Kahu / Husna Raaina Mad Hayazi - Mad Hayazi, Husna Raaina (2020)
Your Safety Resources launched YOUR KAHU which is a handy safety kit. KAHU is a Hawaiian origin word that best describe as GUARDIAN. YOUR KAHU is a 4 in 1 safety kit and was made to protect by making sure that everyone is safe especially when they are alone. YOUR KAHU consists of everything you need to make sure you are comfortable walking around as the LUMEN LIGHT inside is bright enough to see almost everything and even your shadow is afraid to show up! TASER that we designed operate effectively and neutralize an attack by people or even animals. Personal ALARM is perfect to quickly attract attention in an emergency situation. The sleek alarm features a piercing 120dB siren, equivalent to the sound of a chain saw. It can be heard up to 300 feet away, which is the length of a football field. Your safety kit is almost complete as we also provide PEPPER SPRAY, it is classified as an inflammatory agent and will immediately incapacitate an assailant. Now everyone can be safe without afraid to walk alone! Our company promised to sell this safety kit at an affordable price so that everyone can own it without hesitation. We target to produce 10,000 units on our first year of production and a closing sales of RM 750,000.00. Our management team is led by experience leader in their own field to ensure product quality are beyond customer’s expectation.